Characterization of Acetamiprid Biodegradation by the Microbial Consortium ACE-3 Enriched From Contaminated Soil - Xu, Bin; Xue, Rui; Zhou, Jie; Wen, Xin; Shi, Zhoukun; Chen, Minjiao; Xin, Fengxue; Zhang, Wenming; Dong, Weiliang; Jiang, Min (Frontiers in Microbiology, 2020)
Microbial consortia are ubiquitous in nature and exhibit several attractive features such as sophisticated metabolic capabilities and strong environmental robustness. This study aimed to decipher the metabolic and ecological characteristics of synergistic interactions in acetamiprid-degrading consortia, suggesting an optimal scheme for bioremediation of organic pollutants. The microbial consortium ACE-3 with excellent acetamiprid-degrading ability was enriched from the soil of an acetamiprid-contaminated site and characterized using high-throughput sequencing (HTS). Consortium ACE-3 was able to completely degrade 50 mg·L-1 acetamiprid in 144 h, and was metabolically active at a wide range of pH values (6.0-8.0) and temperatures (20-42°C). Furthermore, plausible metabolic routes of acetamiprid biodegradation by the consortium were proposed based on the identification of intermediate metabolites (Compounds I, II, III and IV). The findings indicated that the consortium ACE-3 has promising potential for the removal and detoxification of pesticides because it produces downstream metabolites (Compound I and II) that are less toxic to mammals and insects than acetamiprid. Finally, Illumina HTS revealed that Proteobacteria were the dominant group, accounting for 85.61% of all sequences at the class level. Among the more than 50 genera identified in consortium ACE-3, Sphingobium, Acinetobacter, Afipia, Stenotrophomonas, and Microbacterium were dominant, respectively accounting for 3.07, 10.01, 24.45 and 49.12% of the total population.